Land use change and its implications on the environment and people's health the case of Mananga Watershed in Metro Cebu, Philippines - Bagarinao, Ricardo T. (Asia Life Sciences : the Asian International Journal of Life Sciences, 2008)
Land use in Mananga Watershed had significantly changed in the past 50 years. As a major source of water and a habitat of many endemic plant and animals in Cebu, the watershed needs to be restored and conserved. The current study was conducted to evaluate the change in its land use between 1956 and 1995, analyze the change patterns and identify their implications on the environment and people's health. The analysis was conducted through the use of GIS. Results of the study show that the watershed was covered predominantly with annual crops in 1956 but with brushland and tree plantation in 1995. Annual cropland areas had decreased by 42% while both brushland and tree plantation increased by 102 and 73%, respectively in 1995. This change in land cover should be attributed to the series of reforestation activities in the watershed. These activities may potentially result to the following: (1)reduction in soil erosion and siltation in rivers and creeks; (2) adequate recharge for the aquifers that are supported by the watershed and (3) water contamination by chemicals from mango plantations. However, the actual impact of land use change may not be observed immediately and hence, require further studies and monitoring.